Biochemical Changes Induced By Cadmium, Copper, Lead And Zinc Exposure To Perna Viridis Under Longterm Toxicity Test - J.S.I RAJKUMAR; M.C JOHN MILTON (International Journal of Pharma and Bio Sciences, 2011)
Environmental pollution is a growing concern and, more importantly, pollution of the aquatic ecosystem is alarming. Bivalves are commonly used as bio-indicators of marine pollution. In the present study the Perna viridis was exposed to cadmium, copper, lead and zinc concentrations under longterm chronic toxicity for the estimation of biochemical biomarkers. Significant differences in TBARS levels and antioxidant enzyme activity were found. Higher levels of TBARS were found with cadmium exposure. This study suggests that TBARS levels and antioxidant enzymes activity are affected by biotic and abiotic factors and have potential as indicators of heavy metal contamination. Since these results were also found to vary, the determination of oxidative stress biomarkers in Perna viridis may serve as a convenient approach during pollution biomonitoring programme.